High Intensity Interval Training in Handcycling: The Effects of a 7 Week Training Intervention in Able-bodied Men - Schoenmakers, Patrick; Reed, Kate; Van Der Woude, Luc; Hettinga, Florentina J. (Frontiers in Physiology, 2016)
INTRODUCTION: In lower body endurance training, quantities of both moderate intensity continuous training (MICT) and high intensity interval training (HIIT) can lead to an improved physiological capacity and performance. Limited research is available regarding the endurance and muscular capacity of the upper body, and how training contributes to improvements in performance capacity is still unknown. The aim of the current study was to evaluate the effects of HIIT and MICT on the physiological capacity and handcycling performance of able-bodied men in a well-controlled laboratory setting. METHODS: 24 recreationally active men (22 ± 2 years; 1.84 ± 0.04 m; 79 ± 10 kg) were matched on incremental handcycling pre-test performance (peakPO) and then randomly assigned to HIIT, MICT or a non-training control group (CON, 3 x n=8). Participants in HIIT completed 14 interval training sessions, performing 4x4 minute intervals at 85 % heart rate reserve (%HRR), and 7 continuous training sessions at 55 %HRR (every 2nd training session of the week). Participants in MICT performed 21 training sessions of 30 minutes on 55 %HRR. After the intervention, changes in peak oxygen uptake (peakVO2) and peak power output (peakPO) were compared within and between HIIT, MICT and CON. RESULTS: The average external training load per training session did not differ between MICT and HIIT (p=0.713). Improvements after HIIT in peakVO2 (22.2 ± 8.1%) and peakPO (47.1 ± 20.7%) were significantly larger compared with MICT and CON (p<0.001). Improvements after MICT in peakVO2 (10.7 ± 12.9%) and peakPO (32.2 ± 8.1%) were higher compared to CON (p<0.001). Higher improvement after HIIT occurred despite training 22% less time than MICT. No significant changes were found in CON. DISCUSSION: As in lower body endurance sports, HIIT proved to be very effective in improving the physiological and performance capacity of upper body exercise. Whilst physiological capacity in both training groups improved significantly compared with CON, the present study shows that peakVO2 and peakPO improved more after HIIT than after MICT in able-bodied men. It is advised to include HIIT into training regimes of recreational and competitive handcyclists to improve upper body endurance capacity.